Predictors of Persistent Participation in Youth Sport: A Systematic Review and Meta-Analysis - Zhang, Meng; Wang, Xiao-Chun; Shao, Bin (Frontiers in Psychology, 2022)
There are many factors affecting decisions to persistent participation in sports and various approaches have been used to frame these antecedents. The aim of this paper was to systematically review and quantify the primary factors of persistent participation and to assess their respective strengths of association with persistent participation in youth sport. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guidelines, a comprehensive search was implemented on 31st December 2021 in five databases and meta-analytic procedures were applied to data from studies meeting inclusion criteria. The results revealed that sports enjoyment, parental support, coach support, peer support, basic psychological needs and sports competence were the primary factors associated with persistent intention and persistent behavior, respectively. In addition, sports enjoyment (meta r=0.45, 95%CI[0.42, 0.49]) was highly correlated with persistent intention, while sports enjoyment (SMD=0.88, 95%CI[0.60, 1.18]) and persistent intention (SMD=0.80, 95%CI[0.71, 0.90]) were highly correlated with persistent behavior. This study identified the key factors related to persistent participation and provide a complete understanding of children and adolescents’ decisions to continue their participation in organized sports. Referring to the key factors, it can provide information for sports clubs and policy makers to develop strategies to increase youth participation in organized sport.